Treatment of three-level cervical spondylotic myelopathy using ACDF or a combination of ACDF and ACCF - Tian, Xiaoming; Zhao, Hongwei; Han, Felicity Y.; Rudd, Samuel; Li, Zhaohui; Ding, Wenyuan; Yang, Sidong (Frontiers in Surgery, 2022)
Objectives: This study aims to compare the outcomes between two anterior decompression and fusion techniques to treat multilevel cervical spondylotic myelopathy (MCSM). Methods: After the screening for eligibility, a total of 66 patients were admitted to this study. These participants underwent anterior surgeries due to MCSM in our hospital between June 2016 and July 2018. All participants underwent either the anterior cervical discectomy and fusion (ACDF) surgery (ACDF group) or the combination of ACDF and anterior cervical corpectomy and fusion (ACCF), which was the anterior cervical hybrid decompression and fusion (ACHDF) surgery group. The follow-up time of these participants was 23.64 (±2.69) months. The length of hospitalization, operation time, blood loss, visual analog scale (VAS), Japanese Orthopaedic Association (JOA) score, improvement rate, Hounsfield units (HU) of C3-C7, cobb angle, and anterior column height of fusion levels pre and post operation were analyzed. Results: There were no statistical differences between the ACDF and ACHDF groups regarding the length of hospitalization, operation time, blood loss, HU of C3-C7, VAS, JOA score, improvement rate, cobb angle, and anterior column height in fusion levels in pre-operation and 3 months after operation (all P>0.05). However, compared with the ACHDF group, the ACDF group achieved significantly better improvement in the anterior column height of fusion levels in the final 18-29 months post-operatively (P<0.05). Conclusions: Both approaches of ACDF alone and a combination of ACDF and ACCF can achieve satisfactory outcomes in the treatment of MCSM, but ACDF has better outcomes in maintaining anterior column height of fusion levels.